2007
DOI: 10.1055/s-2006-927153
|View full text |Cite
|
Sign up to set email alerts
|

Lokale Applikation von Mitomycin C zur Behandlung einer Ösophagusstriktur nach Laugenverätzung bei einem 4-jährigen Jungen

Abstract: Accidental caustic ingestion is a common problem in young children at the age of 1 to 4 years. In cases of circular injuries of the oesophagus subsequent strictures can arise. Endoscopic balloon dilatation is the commonly used intervention but does not always lead to permanent improvement. We report the successful use of mitomycin C in a young boy in whom we could achieve ongoing relief of dysphagia after the unsuccessful long-term use of frequent endoscopic dilatations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Mitomycin-C, an antibiotic used as an antineoplastic and antifibrotic agent, has been previously used in topical applications to prevent scar formation and recurrence of stricture after ophthalmological surgery (4), in recurrent laryngeal and tracheal stenosis (5), and after dacryocystorhinostomy (6). A few small series (7)(8)(9) and case reports (10)(11)(12)(13)(14) have also suggested that mitomycin-C could have a prophylactic role in avoiding postoperative fibrosis when used in patients with esophageal strictures of various origins (peptic, caustic, postoperative). In these series, only a few cases of esophageal stricture following surgery for congenital EA have been reported.…”
mentioning
confidence: 99%
“…Mitomycin-C, an antibiotic used as an antineoplastic and antifibrotic agent, has been previously used in topical applications to prevent scar formation and recurrence of stricture after ophthalmological surgery (4), in recurrent laryngeal and tracheal stenosis (5), and after dacryocystorhinostomy (6). A few small series (7)(8)(9) and case reports (10)(11)(12)(13)(14) have also suggested that mitomycin-C could have a prophylactic role in avoiding postoperative fibrosis when used in patients with esophageal strictures of various origins (peptic, caustic, postoperative). In these series, only a few cases of esophageal stricture following surgery for congenital EA have been reported.…”
mentioning
confidence: 99%